School connectedness, peer attachment, and self-esteem as predictors of adolescent depression - Millings, Abigail; Buck, Rhiannon; Montgomery, Alan; Spears, Melissa; Stallard, Paul (Journal of adolescence (London, England.), 2012)
Recent literature suggests that school connectedness (SC) may be a key determinant of adolescent mental health. Specifically, SC has been found to have a negative relationship with adolescent depression. In the current, cross sectional study, we examine whether the relationship between SC and symptoms of low mood is dampened or moderated by self-esteem (SE) and peer attachment style. Participants were 5022 adolescents (aged 11–16) who completed a battery of questionnaires in school, including measures of low mood, SC, SE, and peer attachment style. The relationship between SC and low mood was reduced by the inclusion of SE and peer attachment style. Peer attachment style was the largest predictor of low mood. The relationship between SC and low mood was not moderated by SE or peer attachment style. Interventions for adolescent depression may be most effective by focussing on increasing SE and fostering secure attachments, rather than solely focussing on increasing SC.